Clinical decision analysis and model‐based economic evaluation studies in perinatology: A systematic review. (4th April 2019) - D'Souza, Rohan; Bonasia, Kyra; Shah, Prakesh S.; Murphy, Kellie E.; Sander, Beate
Abstract: Introduction: Perinatology, the study of two individuals that constitute the mother‐fetus dyad, poses unique challenges to the conduct of clinical decision analysis (CDA) and economic evaluation (EE) studies. Our objective was systematically to review CDA and model‐based EE studies in pregnant women to better understand how these studies have been conducted and reported in perinatology. Material and methods: MEDLINE, Embase, Scopus, Web of Science and clinicaltrials.gov were searched as of October 2018. The indexing terms "pregnancy", "decision trees", "Markov models" and "economic models" were used. The search was limited to human data and the English language. Two reviewers independently screened titles and abstracts. Data extraction and assessment of reporting quality were performed in duplicate for 10% of studies and reached 100% agreement. The remainder was carried out by a single reviewer. The study protocol was registered with PROSPERO (CRD 42016047206). Results: Seventy‐seven studies met eligibility criteria and fulfilled between 40% and 91% of relevant attributes on the checklist for critical appraisal of CDA models. There was considerable variation in study reporting. A total of 53% of studies included maternal and offspring outcomes, 14% described using weighted means, meta‐analyses or health administrative databases to estimate probabilities and 13% considered outcomes over the lifetime of mother and offspring. Patient preferences (utilities) were used in 47% of the studies. Of these, 10% were elicited from healthcare providers alone and not from pregnant women or the public. Of the EE studies, 25% described a societal analytic perspective. Where relevant, 42% described discounting for costs and benefits, and 30% reported using probabilistic and deterministic sensitivity analyses. Conclusions: Despite long‐term implications of perinatal decisions to mother and offspring, CDA and model‐based EE studies in perinatology frequently do not consider lifetime horizons and patient‐preferences for outcomes related to mother and offspring. They also often fail to adhere to guidelines regarding conduct and reporting.